Kesejahteraan Psikologis Siswa SMK: Peran Dukungan Keluarga, Sekolah, dan Lingkungan Sosial Muslim serta Efikasi Diri - Aliya Bintang Kurnia; I Rheny Arum Permitasari; Brigitan Argasiam (Yayasan Azhar Amanaa Yogyakarta, 2026)
Psychological well-being is an important aspect for adolescents in facing academic and social demands, including for Vocational High School (SMK) students who are also confronted with the demands of vocational practice and job readiness. This study aims to determine the relationship between social support and self-efficacy with psychological well-being among eleventh-grade students at SMK Negeri 4 Semarang. The study used a quantitative correlational approach with a simple random sampling technique on 292 students from a population of 612 students. Data were collected using three Likert scales—namely the social support, self-efficacy, and psychological well-being scales—and then analyzed using multiple linear regression with the assistance of SPSS version 26.0. The results showed that social support was positively and significantly related to psychological well-being (t = 10.223; p < 0.05), self-efficacy was positively and significantly related to psychological well-being (t = 31.714; p < 0.05), and social support and self-efficacy simultaneously had a significant relationship with psychological well-being (F = 680.989; p < 0.05), accounting for 82.5% of the variance. Self-efficacy made a more dominant contribution (70.45%) compared to social support (12.09%). These findings confirm the importance of strengthening students' internal factors in efforts to improve psychological well-being at the vocational education level. These findings also highlight the importance of family, school, and the Muslim social environment as sources of psychological support for students.